2023
DOI: 10.2478/rtuect-2023-0026
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining a Mars Colony through Integration of Single-Cell Oil in Biological Life Support Systems

Abstract: As humanity sets its sights on establishing a sustainable and prosperous colony on Mars, the main challenges to be overcome are ensuring a reliable and nutritious food supply for settlers, feedstock for 3D printing, fuel and pharmaceuticals. While various solutions for production of essential products on Mars have been proposed, there is growing interest in the use of microorganisms as the main production units. This scientific review article proposes a novel concept of using single cell oil (SCO) as a versati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 212 publications
0
1
0
Order By: Relevance
“…Linking the multi-criteria analysis to the sustainability pillars, it can be concluded that the results with sustainable aquaculture and fisheries products were in line with the economic sustainability pillar as well as the social and environmental pillars. At the moment, Latvia is on the way to developing the aquaculture sector, which can be justified by the development of new companies in Latvia (SpirulinaNord), the inclusion of new products on the market and the important scientific research (K. Spalvins et al [62]) being carried out to think about the growing demand for easily obtainable proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Linking the multi-criteria analysis to the sustainability pillars, it can be concluded that the results with sustainable aquaculture and fisheries products were in line with the economic sustainability pillar as well as the social and environmental pillars. At the moment, Latvia is on the way to developing the aquaculture sector, which can be justified by the development of new companies in Latvia (SpirulinaNord), the inclusion of new products on the market and the important scientific research (K. Spalvins et al [62]) being carried out to think about the growing demand for easily obtainable proteins.…”
Section: Discussionmentioning
confidence: 99%